The Impacts of Integrative and Instrumental Motivation for Indonesian Learners - Syafrizal Syafrizal (Universitas Negeri Yogyakarta, 2020)
Motivation plays an important role in foreign language learning. This paper discusses the definition of motivation, types of motivation; the factors influencing motivation in learning English, and Gardner’s socioeducational model. The purpose of the study was to find out the the impact of integrative and instrumental motivation in learning English. This study applied descriptive quantitative method. Using a purposive sampling technique, obtained the 20 respondents who met the requirements. The subjects in this study were seventh grade students of SMPIT Putri Al-Hanif. The writer designed a questionnaire of motivation by using likert scale. To achieve the goal, Gardner and Lambert's model were taken into consideration. They were distributed among students by simply evaluating 20 statements. Results indicated that seventh grade students of SMPIT Putri Al-Hanif have stronger integrative motivation than instrumental motivation.